Burden of Influenza in 4 Ecologically Distinct Regions of Peru: Household Active Surveillance of a Community Cohort, 2009–2015. (9th August 2017) - Tinoco, Yeny O; Azziz-Baumgartner, Eduardo; Uyeki, Timothy M; Rázuri, Hugo R; Kasper, Matthew R; Romero, Candice; Silva, Maria E; Simons, Mark P; Soto, Giselle M; Widdowson, Marc-Alain; Gilman, Robert H; Bausch, Daniel G; et al.
Abstract : This study describes population-based estimates for quantifying influenza disease burden, health utilization patterns among participants of all ages, and seasonality in different climactic regions. Findings will help place global influenza burden of disease models into better context by providing case-based incidence. Abstract: Background: There are limited data on the burden of disease posed by influenza in low- and middle-income countries. Furthermore, most estimates of influenza disease burden worldwide rely on passive sentinel surveillance at health clinics and hospitals that lack accurate population denominators. Methods: We documented influenza incidence, seasonality, health-system utilization with influenza illness, and vaccination coverage through active community-based surveillance in 4 ecologically distinct regions of Peru over 6 years. Approximately 7200 people in 1500 randomly selected households were visited 3 times per week. Naso- and oropharyngeal swabs were collected from persons with influenza-like illness and tested for influenza virus by real-time reverse-transcription polymerase chain reaction. Results: We followed participants for 35353 person-years (PY). The overall incidence of influenza was 100 per 1000 PY (95% confidence interval [CI], 97–104) and was highest in children aged 2–4 years (256/1000 PY [95% CI, 236–277]). Seasonal incidence trends were similar across sites, with 61% of annual influenza cases occurring during the austral winter (May–September). Of all participants, 44 per 1000 PY (95% CI, 42–46) sought medical care, 0.7 per 1000 PY (95% CI, 0.4–1.0) were hospitalized, and 1 person died (2.8/100000 PY). Influenza vaccine coverage was 27% among children aged 6–23 months and 26% among persons aged ≥65 years. Conclusions: Our results indicate that 1 in 10 persons develops influenza each year in Peru, with the highest incidence in young children. Active community-based surveillance allows for a better understanding of the true burden and seasonality of disease that is essential to plan the optimal target groups, timing, and cost of national influenza vaccination programs.